Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/pcn.12684
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oxygenated hemoglobin concentration change during pleasant and unpleasant image‐recall tasks in patients with depression: Comparison with healthy subjects

Abstract: We suggest that image-recall tasks related to emotion measured by NIRS might be a visually useful psychophysiological marker to understand the decrease in the frontal lobe function in MDD patients. In particular, we suggest that the decrease in δoxyHb in the left frontal lobe is related to the severity of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…When subjects were performing right-finger-tapping tasks, the increase in oxy-Hb was higher in the depressed patients when comparing with HCs (18). In the image-recall task, the change in oxy-Hb in the HCs was considerably more than in the depressed while experiencing unpleasant conditions (53).…”
Section: Use Of Fnirs To Differentiate Depressed From Healthy Individmentioning
confidence: 86%
“…When subjects were performing right-finger-tapping tasks, the increase in oxy-Hb was higher in the depressed patients when comparing with HCs (18). In the image-recall task, the change in oxy-Hb in the HCs was considerably more than in the depressed while experiencing unpleasant conditions (53).…”
Section: Use Of Fnirs To Differentiate Depressed From Healthy Individmentioning
confidence: 86%
“…Despite the gradual clarification of the biological aspects of depression, [34][35][36][37][38][39][40] the biological basis of depression-related personality traits has not been well clarified. Tryptophan metabolites, especially serotonin, have gathered greater attention in the endeavor to understand the pathophysiology of depression.…”
Section: Fourth Step: Pilot Analysis Of Biological Validitymentioning
confidence: 99%
“…It has been found that the brain functions of A&D are different from either depression or anxiety alone. Patients with depression have the suppressed functions of brain regions that regulate emotion and cognition, thus exhibiting the relevant clinical symptoms (3,4). By contrast, the alterations in cerebral cortex function occur in specific regions for A&D patients, particularly in the prefrontal lobe and temporal lobe, affecting execution, language, memory, and attention, as evidenced by the declined cognitive control ability (5).…”
Section: Introductionmentioning
confidence: 99%